d-STATISTICAL CONVERGENCE OF ORDER ? AND d-STATISTICAL BOUNDEDNESS OF ORDER ? IN METRIC SPACES - Kayan, Emine; Colak, Rifat; Altin, Yavuz (Univ Politehnica Bucharest, Sci Bull, 2018)
In the present paper, we introduce and study d-statistical convergence of order alpha d-statistical boundedness of order a and d-strong p - Cesaro summability of order alpha for sequences in a metric space. Furthermore, we investigate the relations between the sets of sequences which are d-statistically convergent of order alpha, between the sets of sequences which are d-statistically bounded of order a and between the sets of sequences which are d-strongly p - Cesaro summable of order alpha for various values of alpha' s in (0,1].
Keywords: alpha-density; statistical convergence; statistical convergence of order alpha; statistical boundedness of order alpha; strong p - Cesaro summability of order alpha